Immunogenomic Analyses of the Prognostic Predictive Model for Patients With Renal Cancer - Feng, Tao; Zhao, Jiahui; Wei, Dechao; Guo, Pengju; Yang, Xiaobing; Li, Qiankun; Fang, Zhou; Wei, Ziheng; Li, Mingchuan; Jiang, Yongguang; Luo, Yong (Frontiers in Immunology, 2021)
Background: Renal cell carcinoma (RCC) is associated with poor prognostic outcomes. The current stratifying system does not predict prognostic outcomes and therapeutic benefits precisely for RCC patients. Methods: Herein, an immune prognostic signature was developed, and its predictive ability was confirmed in the cohorts based on TCGA-KIRC dataset. Several immunogenomic analyses were conducted to investigate the correlations between immune risk scores and immune cell infiltrations, immune checkpoints, cancer genotypes, tumor mutational burden, and responses to chemotherapy and immunotherapy. Results: The immune prognostic signature contained 14 immune-associated genes and was found to be an independent prognostic factor for KIRC. Furthermore, the immune risk score was established as a novel marker for predicting the overall survival outcomes for RCC. The risk score was correlated with some significant immunophenotypic factors, including T cell infiltration, antitumor immunity, antitumor response, oncogenic pathways, and immunotherapeutic and chemotherapeutic response. Conclusions: The immune prognostic, predictive model can be effectively and efficiently used in the prediction of survival outcomes and immunotherapeutic responses of RCC patients.